Decision support system for cow-calf producers - Brigham, Brian W., author; Enns, Richard M., advisor; Garrick, Dorian, committee member; Frasier, Marshall, committee member (Colorado State University. Libraries, 2011)
Sire selection is an important decision directly affecting ranch profitability. The need for decision-support software is increasing with the growing number of EPD available. The objective of this project was to develop web-based tools to evaluate production and economic outcomes from the use of alternative sires. A model which simulates the age structure of a herd to predict performance, revenues and costs while accounting for non-genetic effects such as age of the dam was constructed. Users provide a minimum number of production inputs comprising herd size, pregnancy rate, replacement rate, mature cow size, calf survival, birth and weaning weights. These define an equilibrium age structure and provide realistic production outcomes for the base herd. Genetic variables that simultaneously influence model behavior are limited to those economically relevant traits that are closely aligned to available EPD. These include heifer pregnancy, calving ease direct and maternal, mature cow size, cow maintenance requirements, stayability, birth, weaning and yearling weights as well as weaning weight maternal. These EPD are used to derive a new equilibrium age structure and corresponding performance levels following perturbation of the base situation. The total number of cows is then modified, accounting for any change in feed requirements, to provide annual feed consumption identical to the base herd. Outputs from the model allow a producer to compare current herd production and economic performances to those predicted if alternative sires had been used and the system allowed to re-equilibrate. Primary differences in revenue come from changes to the number and weight of sale calves. Other contributions to variation in revenue are from values of cull cows, replacement costs and dystocia costs. Primary differences in operation costs come from the number of replacements required and the feed requirements of the predicted herd. Discounting procedures are not included. In contrast to other models, the software provides for sire selection by simulation rather than simply generating economic values for subsequent use.
Keywords: decisions support; sire selection; genetics